Self-replicating RNA viruses in vaccine development - Kenneth Lundstrom (Open Exploration Publishing Inc., 2023)
Self-replicating RNA viruses such as alphaviruses, flaviviruses, paramyxoviruses, and rhabdoviruses have been engineered as expression vectors for vaccine development. The prominent feature of self-replicating RNA viruses is their RNA-dependent RNA polymerase activity, which generates massive self-amplification of RNA in the cytoplasm of infected host cells leading to extreme levels of transgene expression. Infectious diseases have been targeted by overexpression of surface proteins of pathogens as antigens for vaccine development. Moreover, overexpression of tumor-associated antigens and immunostimulatory genes has been the basis for cancer vaccines. Proof-of-concept of robust antigen-specific immune responses and protection against challenges with lethal doses of infectious agents have been demonstrated. Likewise, vaccine development against various cancers has elicited strong immune responses and resulted in tumor regression and eradication, cure, and prolonged survival in animal tumor models. Good safety and immune responses have been achieved in clinical trials. The ERVEBO® vaccine, based on the vesicular stomatitis virus, has been approved for immunization against the Ebola virus disease.